Perancangan Sistem Pengelolaan Ruang Wisma Dosen Berbasis Android di Universitas Nurul Jadid - Fajrullah Fajrullah; Fathorazi Nur Fajri; Wahab Sya'roni (Universitas Nurul Jadid, 2020)
The rooms at the Nurul Jadid University lecturers' guest house still could be borrowed only by asking for information to the room desk. It makes the borrower wasting a lot of time, especially if the room desk is not available, in which the borrower needs to wait for getting the certainty of approval for the room borrowing schedule, and dealing with the frequent crashes because there is no system with effective borrowing management. Therefore, this program is to make an Android-based Space Borrowing Management Application by which the user can make use of its features to manage the room and make it easier to borrow the room.